Mixed Methods Approach to Ergonomic Risk Assessment in Malaysian Railway Maintenance Operations - Hellstrome Young Akuma; Nazlin Hanie Abdullah (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2025)
The safety and well-being of human personnel play an increasingly important role in determining whether prescribed objectives and overall performance goals are met in work environments. Various Ergonomic Risk Assessment (ERA) methodologies are thus constantly applied to examine whether risks and hazards that can lead to musculoskeletal disorders (MSDs) are present in these environments. This is especially true in high-risk industries, such as railway maintenance, where workers are subjected to repetitive tasks that are often dynamic and complex in nature. This study, therefore, proposes a conceptual framework to assess ergonomic risk factors (ERFs) in such environments, and suggests mechanisms for intervention. To achieve this, a Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) was used to collect pain and discomfort data from 27 Malaysian railway maintenance workers (n=27). This was supported by semi-structured interviews, which provided context for the numerical results and incorporated workers’ perceptions of their routine tasks into the overall study design. Findings from the collected data showed that workers were often exposed to ERFs, including awkward and static postures over long periods of time. Pain and discomfort were also reported in upper body regions, including the shoulders, neck, and wrists. These results exposed the need for the incorporation of modern technological tools to support the assessment process. The proposed framework, therefore, sets a stage for the integration of Three-Dimensional Computer-Aided Design (3D-CAD) and Virtual Reality (VR) as simulation and visualization components of ERA.